THE SEMIOTIC TRANSCODING OF THE EMOTION OF FEAR: A PRAGMASTYLISTIC ANALYSIS OF FEAR IN THOMAS HARRIS’S RED DRAGON AND ITS MULTIMODAL REALIZATION - Ollomurodov Arjunbek Orifjonovich (International Journal of Literature and Language Studies, 2026)
This article investigates the complex linguistic and semiotic mechanisms utilized to encode the emotion of fear within Thomas Harris’s Red Dragon (1981) and evaluates the